STUDY OF ANTIBACTERIAL PROPERTIES CHRYSANTHEMUM X KOREANUM MAKAI AND CHRYSANTHEMUM INDICUM L - Olga Andreevna Andreeva; Nadezhda Vasilievna Postnikova; Vsevolod Leonidovich Adzhienko; Maksim Ivanovich Kodonidi (Современная наука и инновации, 2022)
The results of the study antibacterial properties of the dry extracts obtained with ethyl alcohol of different concentration of Korean chrysanthemum (Chrysanthemum x koreanum Makai) and Indian chrysanthemum (Chrysanthemum indicum L.) of the Compositae family (Asteraceae) against the 12 test cultures. The largest spectrum of antibacterial activity detected in the extract of flowers Chrysanthemum indicum L. received 70% ethyl alcohol.